Computational fluid dynamics simulation of an anterior communicating artery ruptured during angiography. (14th March 2013) - Hodis, Simona; Uthamaraj, Susheil; Lanzino, Giuseppe; Kallmes, David F; Dragomir-Daescu, Dan
Abstract : We present a computational fluid dynamics (CFD) analysis of the hemodynamic environment of an anterior communicating artery that spontaneously ruptured immediately following three-dimensional rotational angiography. Subsequent digital subtraction angiography allowed for the localization of the point of rupture within the aneurysm dome. CFD analysis demonstrated a concentrated jet that impinged directly at the site of rupture. Peak systolic pressure and wall shear stress were both maximal near the rupture location.